Radiosurgery of brain cavernomas--long-term results - Liscak, Roman (Progress in neurological surgery, 2013)
The radiosurgery of cavernomas remains a controversial issue. The only way to verify the positive effect of the treatment is by clinical observation during a longer follow-up period, where a decreased annual risk of rebleeding should be observed after the latent interval inherent to radiosurgery. Besides this, an improvement in clinical symptoms (e.g. secondary epilepsy) and regression of the treated lesion might also be observed. In a group of 112 patients with brain cavernomas treated in our centre between 1992 and 2000 with the marginal dose of a median 16 Gy, the risk of bleeding decreased from 2% before the treatment to 0.5% after 2 years' latent interval (median follow-up 84 months). A decrease in the extent of the cavernoma was observed in 53% of cases and an increase in 6.4%. Epilepsy, if present before the treatment, improved in 45% of cases. The risk of temporary and permanent morbidity caused by radiosurgery was 14.6 and 0.9%, respectively. This morbidity can be reduced by a lower marginal dose, and future studies should show if repeated radiosurgery decreases the risks from a natural course of the disease in those cases where the initial radiosurgery failed.
Keywords: dospělí; Female; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; Adolescent; Time Factors; časové faktory; lidé; Hemangioma, Cavernous, Central Nervous System; pooperační komplikace; Treatment Outcome; Aged, 80 and over; následné studie; radiochirurgie; Radiosurgery; kavernózní hemangiom centrálního nervového systému; Follow-Up Studies; Male; Postoperative Complications; Aged; Young Adult; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; mladiství; Humans